Reaction of folic acid with reducing sugars and sugar degradation products - Schneider, Marc; Klotzsche, Marcus; Werzinger, Christoph; Hegele, Jörg; Waibel, Reiner; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2002)
The reaction of folic acid with reducing sugars (nonenzymatic glycation) under conditions that can occur during food processing and preparation was studied by high-performance liquid chromatography with diode array detection. N-(p-Aminobenzoyl)-L-glutamic acid, a well-established oxidation product, was detected in the reaction mixtures. Furthermore, a new product was isolated and identified as N2-[1-(carboxyethyl)]folic acid (CEF). CEF was the main product that was formed by the nonenzymatic glycation of folic acid. For preparation, N2-[1-(carboxyethyl)]folic acid was obtained in high yields when folic acid and dihydroxyacetone (DHA), a sugar degradation product, were heated at 100°C in phosphate buffer. Mixtures of folic acid and different sugars or DHA were heated under variation of reaction time and temperature, and CEF was quantified. Up to 50% of the vitamin was converted to CEF, with highest yields formed from maltose (49%) and lactose (43%).
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.reacti
Keywords: Folate degradation; Folic acid; HPLC; Maillard reaction; N; Nonenzymatic glycation